Study of anemia types in the blood parameters among children of Baqubah city - Amjad Adham Ahmed; Hameed Mahmood Majeed (Diyala Journal of Medicine, 2018)
Background: Anemia is the most common condition in blood diseases, is caused by              a decrease in hemoglobin concentration on normal level .